The effect of vascular endothelial growth factor (VEGF) expression on prognosis of patients with colorectal carcinoma [Kolo-rektal kanserlerde vasküler endoteli̇al büyüme faktörü (VEBF) ekspresyonunun prognoz üzeri̇ne etki̇si̇] - (:unkn) unknown (My University, 2005)
Objective: In patients with stages A-B colorectal carcinoma there is still low but potential risk of local recurrence and metastatic disease to some extend after colorectal resection for curative intent. So new prognostic markers are necessary to select the patients with colorectal cancer, who may have benefit from the adjuvant therapies Methods: Among 119 patients, classified as stage A or B1-2 according to modified Astler-Coller, 41 patients with regular follow-up were selected for this study, 16 of whom had local recurrences or distant metastases. VEGF expressions were detected with biotinated anti-rabbit immunoglobulin staining. Results: No statistical survival benefit was found between VEGF positive and negative groups; 82.13% and 83.33% respectively. Also no association between VEGF expression and tumor localization, clinical presentation, depth of tumor invasion, tumor grade, angioneural-lymphatic invasion, local recurrences or distant metastases and survival were detected. Conclusion: As a conclusion of this study, no prognostic significance of immunohistochemically detected tumoral angiogenesis in stage A or B colorectal carcinoma was proven.
Keywords: Angiogenesis; Colon cancer; Vascular endothelial growth factor